2021
DOI: 10.1111/trf.16409
|View full text |Cite
|
Sign up to set email alerts
|

Demographic, clinical, and biochemical predictors of pica in a large cohort of blood donors

Abstract: Background: Pica is characterized as repeatedly eating or chewing a nonnutritious substance including, but not limited to ice, clay and dirt, starch, raw pasta, chalk, coal, paint, or paper. Pica symptoms can be intense and addiction-like and disrupt quality of life. It is strongly linked to iron deficiency. Since substantial iron loss occurs during blood donation, blood donors may be susceptible to development of pica behaviors.Methods: We investigated demographic, clinical, hematological, and biochemical fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 34 publications
0
16
1
Order By: Relevance
“…A study by Liu et al . (2021), e.g. highlighted that pica might be related to a complex comorbidity structure, insofar as it is strongly associated with restless legs syndrome, which, in turn, is associated with depressive symptoms (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Liu et al . (2021), e.g. highlighted that pica might be related to a complex comorbidity structure, insofar as it is strongly associated with restless legs syndrome, which, in turn, is associated with depressive symptoms (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This cohort contained 1748 high‐intensity donors who gave nine or more units of whole blood in the preceding 2 years without experiencing a low haemoglobin deferral 8 . High intensity donors have many demographic and behavioural differences compared to the general donor population and are less likely to experience haemoglobin deferral 6,8 . To better understand pica symptoms in this important group of donors, we characterised the demographic, clinical, and biochemical predictors of pica in these high‐intensity donors and compared these to predictors of pica in the remainder of the RBC‐Omics study population 6 …”
Section: Introductionmentioning
confidence: 99%
“…Pica is defined as excessive craving and chewing of non‐nutritious substances such as ice, clay, earth, paper, or chalk 2 . Depending on the classification, it has been estimated that from 2% to 15% of blood donors in the United States report pica symptoms 3–6 . In the United Kingdom, the reported prevalence of pica in blood donors is significantly lower because of the lower prevalence of chewing ice, and estimated to be between 0.65% and 1.83% 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Pica, the compulsive craving, and ingestion of nonnutritive substances is associated with iron depletion in general [47] and blood donor [6,7] populations. Pica was present in 2.2% of a mostly representative United States donor population and associated with low ferritin as well as RLS [9]. In several donor studies, an association between iron and RLS was not found [6,7,48] but one recent study reported improvements in RLS, sleep, and fatigue following use of exogenous iron [49].…”
Section: Impact Of Iron Deficiency On Blood Donor Healthmentioning
confidence: 99%
“…Consequently, donors of both sexes become iron-deficient [3]. The symptoms of iron deficiency are substantial, including fatigue [4,5], pica [6][7][8][9], and restless leg syndrome (RLS) [6,7,[9][10][11]. Here, we review recent advances in the understanding of iron deficiency in blood donors, and how it is successfully mitigated.…”
Section: Introductionmentioning
confidence: 99%